Water Quality Evaluation of Post-Tin Mining Ponds Tourism in Bangka Island Using Diatom as Bioindicator - Rosa Liliani; Catur Retnaningdyah; Endang Arisoesilaningsih (Program Pascasarjana, 2019)
Post tin mining pond in Bangka Island has been used as a tourism place, fishing, fish ponds, and agricultural areas that can reduce water. The purpose of this study is to evaluate quality of water post tin miningpond which is used as a tourist place based on physics, chemical and biotic indices of Diatoms as bioindicator. Sample water and Diatoms were take at 3post tin miningpond (Itam, Pedindang, and Jangkang 2) and natural swamp (Rawa) as reference site. Sampling each pond and swamp wasdone in three stations as replications and then be observed physics-chemical quality of water (pH, water temperature, turbidity, conductivity, COD, and phosphate) and also the Trophic Diatom Index (TDI) and Pollution Tolerant Value (% PTV) from Diatom as indicator of trophic status and organic pollution. The results of the study showed that all of the ponds and natural swamp had low pH range from 4.32-6.34. Turbidity of Itam and Pedindang higher (22-24 NTU) than Jangkang 2 and swamp (3.13-9.13 NTU). Jangkang 2 had the highest conductivity value (115,10 μS.cm-1) and swamp the lowest (10.64 μS.cm-1). The value of COD and total phosphate in all location still fullfilled government standard (COD < 20 mg.L-1 and total phosphate < 0.2 mg.L-1). Water quality in tin mining ponds lower than natural swamps based on Diatom as bioindicator. All of the ponds were categorized as moderately polluted based on Shannon Wiener Diversity index of Diatom (H=1.2-1.6), however swamp have lightly polluted (H=2.6). Trophic status of water in post tin mining pondsbased on Trophic Diatom Index (TDI) included in the eutrophic while in swamp categorized as mesoeutrophic. Based on percentage pollution tolerant value (%PTV), the water in Itam and Pedindang included in heavily organic pollution and water in Jangkang 2 and also swamp have moderately organic pollution.Keywords: Bangka,Diatom, post tin mining pond, tourism, water quality.